South-South University Cooperation: a New Form of Collaboration between Latin America and Africa (Palimpsesto, 2024)
Traditionally, Latin American and African universities cooperated asymmetrically with a (North-South) approach. This article is a work prepared according to a clear objective, which is to examine South-South university cooperation, with a sense of horizontality, rationality and co-responsibility that encourages openness and sharing. For this we have taken as a case study the collaboration of the International Higher Institute of Tourism of Tangier (ISITT) with the Santo Tomas University of Chile (UST) and the Santo Tomas Technical Institute. This example constitutes a successful model of cooperation between African and Latin American university institutions. Our research focuses on exposing how this collaboration has been carried out, what benefits it has brought to both parties and how it has contributed to the development and internationalization of higher education in both countries.